واقع استخدام التكنولوجيا المتنقلة في الإفادة من خدمات المعلومات في مكتبة الجامعة الأردنية من وجهة نظر الطلبة - طه، نشروان ناصر حسن; الشمري، هبه محمود محارب (الجامعة الأردنية - عمادة البحث العلمي, 2019)
The study aimed to identify the reality of using mobile technology in the utilization of information services in the library of University of Jordan from the perspective of students. The study community consisted of the undergraduate students of University of Jordan for the 2017/2016 academic year. The study sample was assigned randomly and contained 381 students .In order to achieve the objectives of the study, a questionnaire that consisted of two parts was developed. The first part included the demographic data of the study sample in light of the following variables: (gender, school year, and college), as for the second part, it consisted of (29) paragraphs divided into three fields to measure the reality of students' usage of mobile technology and the benefits of using information services in the library of University of Jordan. The results showed that using mobile technology for personal recreational purposes and for learning purposes was average. It also indicated that the students 'use of the University of Jordan library site was average as well. The results additionally showed statistically significant differences in the students' usage of mobile technology in educational purposes for the benefit of fourth year students; it also showed a statistical indication of the reality of students' usage of mobile technology in the library site for entertainment purposes for the benefit of females. Based on the results, the study presented a number of recommendations. The most important ones are: the need for officials in the University of Jordan to keep to date with technological developments, to utilize the maximum usage of mobile technology, and to use mobile technology to provide information services to expand the scope of its uses and deliver it to beneficiaries. The study also recommends the necessity to give training classes to students on how to benefit from Information services in the library website.
هدفت هذه الدراسة إلى تعرف واقع استخدام التكنولوجيا المتنقلة في الإفادة من خدمات المعلومات في مكتبة الجامعة الأردنية من وجهة نظر الطلبة، حيث تكون مجتمع الدراسة من طلبة الجامعة الأردنية في مرحلة البكالوريوس للعام الدراسي 2016/2017، وتم اختيار عينة الدراسة بالطريقة العشوائية إذ تكونت من (381) طالبا وطالبة. ولتحقيق أهداف الدراسة، تم بناء استبانة تكونت من قسمين، الأول: تضمن البيانات الديموغرافية لعينة الدراسة في ضوء المتغيرات التالية: (الجنس، والسنة الدراسية، والكلية) وتكون الآخر من: (29) فقرة موزعة على مجالين، تقيس واقع استخدام الطلبة للتكنولوجيا المتنقلة، والإفادة من خدمات المعلومات في مكتبة الجامعة الأردنية. وقد بينت النتائج أن واقع استخدام الطلبة للتكنولوجيا المتنقلة لأغراض تعلميه كان بدرجة متوسطة، وأشارت إلى أن استخدام الطلبة لموقع مكتبة الجامعة الأردنية كان بدرجة متوسطة، وأظهرت وجود فروق ذات دلالة إحصائية عند مستوى (α ≤ 0.05) في استخدام الطلبة للتكنولوجيا المتنقلة في (الأغراض التعلمية) جاء لصالح طلبة السنة الرابعة، وفي مجال (موقع المكتبة) كان لصالح الكلية العلمية. وبناء على هذه النتائج، قدمت الدراسة مجموعة من التوصيات أهمها: ضرورة اهتمام المسؤولين في الجامعات الأردنية بالتطور التقني، والإفادة من التكنولوجيا المتنقلة، واستخدامها في تقديم خدمات المعلومات لتوسيع نطاقها، ووصولها إلى المستفيدين، وضرورة إعطاء دورات تدريبية توعوية للطلبة حول كيفية الإفادة من خدمات المعلومات في موقع مكتبة الجامعة الإلكتروني.
Keywords: التكنولوجيا المتنقلة -- الأردن -- المكتبات الجامعية